CORRELATION BETWEEN STUDENTS’ PREFERENCES ON THEIR TEACHERS’ CODE-SWITCHING AND READING COMPREHENSION PERFORMANCE - William Piter; Bambang A Loeneto; Hariswan Putera Jaya (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: The use of Indonesian language in teaching English practices still becomes an issue. There are teachers who agree with the use of Indonesian language in teaching English practices, but not a few teachers also disagree with it. Therefore, the aim of this study was to find out whether or not there was any significant correlation between students’ preferences on their teachers’ code-switching and reading comprehension achievement of Eighth graders of SMP Tri Dharma Palembang and the contribution from students’ preferences on their teachers’ code-switching to their reading comprehension achievement. The simple random sampling technique was used to get the sample. Therefore, 35 out of 140 students were selected to become the sample of the study. There were 3 instruments which were used in this study. The first instrument was students’ preferences questionnaire to know whether the students have negative or positive tendency toward the use of Indonesian language. The second instrument was teachers’ questionnaire to compare and make sure the validity of the result of the students’ questionnaire. The last instrument was a reading test to measure the students’ reading comprehension achievement. The results of this study were; 1) There were students (88.6%) who had positive tendency toward their teachers’ code-switching, 2) All of the teachers who taught the students agreed that Indonesian language should be used in teaching English, 3) The mean of the students’ reading score was 66.7, 4) There was a significant correlation between students’ preferences on their teachers’ code-switching and students’ reading comprehension achievement (p-value 0.000 < 0.05), 5) The influence of students’ preferences to students’ reading achievement was 40.1%. Keywords: students’ preferences, indonesian language, reading comprehension achievement